A highly regular fucosylated chondroitin sulfate from the sea cucumber Massinium magnum: Structure and effects on coagulation. (1st July 2017) - Ustyuzhanina, Nadezhda E.; Bilan, Maria I.; Dmitrenok, Andrey S.; Borodina, Elizaveta Yu.; Stonik, Valentin A.; Nifantiev, Nikolay E.; Usov, Anatolii I.
Highlights: The structure of the natural fucosylated chondroitin sulfate (FCS) was determined. The sea cucumber Massinium magnum was used as a source of FCS. The backbone of the polysaccharide consists mainly of chondroitin sulfate E units. The only one type of Fuc3 S 4 S branches attached to O-3 of GlcA was found. Anticoagulant and antithrombotic properties of FCS were studied in vitro . Abstract: A fucosylated chondroitin sulfateMM was isolated from the sea cucumber Massinium magnum . Structure of this polysaccharide was determined using chemical and NMR spectroscopic methods. The backbone ofMM was shown to consist mainly of chondroitin sulfate E units with a small portion (about 10%) of chondroitin sulfate A fragments. Practically one type of branches Fuc3S4S attached to O-3 of GlcA residues was found in the polysaccharide molecules. The main repeating units ofMM are →4)-[α-l -Fuc3 S 4 S -(1 → 3)]-β-d -GlcA-(1 → 3)-β-d -GalNAc4 S 6 S -(1→, whereas the minor repeating units are →4)-[α-l -Fuc3 S 4 S -(1 → 3)]-β-d -GlcA-(1 → 3)-β-d -GalNAc4 S -(1→. Anticoagulant activity ofMM determined in APTT and TT tests was shown to be lower than that of heparin, but higher than that of enoxaparin. In the experiments with purified proteinsMM effectively potentiated inhibition of thrombin and factor Xa by ATIII. Besides, MM did not induce platelets aggregation in platelets rich plasma.